2008
DOI: 10.1213/ane.0b013e31817b5ebb
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Study to Evaluate the Efficacy and Safety of Three Different Doses of Palonosetron Versus Placebo for Preventing Postoperative Nausea and Vomiting

Abstract: A single 0.075-mg IV dose of palonosetron significantly increased the CR rate (no emetic episodes and no rescue medication) from 0 to 24 h, decreased nausea severity and patients experienced significantly less interference in their postoperative function due to PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 17 publications
5
108
3
Order By: Relevance
“…In previous studies reported by Candiotti et al 45 and Kovac et al, 46 there was no statistical difference between palonosetron 0.075 mg and placebo in the reduction of PONV during the postoperative 24-72 hr. Compared with ondansetron, the combined results of four studies indicated that palonosetron can significantly reduce the incidence of PON (RR, 0.53; 95% CI, 0.33 to 0.86) but not POV within 24 to 48 or 72 hr after surgery.…”
Section: Early Povmentioning
confidence: 72%
See 1 more Smart Citation
“…In previous studies reported by Candiotti et al 45 and Kovac et al, 46 there was no statistical difference between palonosetron 0.075 mg and placebo in the reduction of PONV during the postoperative 24-72 hr. Compared with ondansetron, the combined results of four studies indicated that palonosetron can significantly reduce the incidence of PON (RR, 0.53; 95% CI, 0.33 to 0.86) but not POV within 24 to 48 or 72 hr after surgery.…”
Section: Early Povmentioning
confidence: 72%
“…43 In contrast, palonosetron thus far appears to be safe in terms of QT intervals. Results of a number of studies [44][45][46] revealed that palonosetron had no effect on the QT interval during surgery. Serotonin syndrome is another serious adverse event associated with the use of 5-HT 3 RAs.…”
Section: A Early Ponmentioning
confidence: 99%
“…patient is exposed to potential side effects from each drug that is administered. Palonosetron, at any dose, has not been found to prolong the QTc interval in contrast to the older 5-HT3 receptors [13]. If administering one drug is as effective as a multi-drug regimen, patient safety is increased without sacrificing efficacy.…”
Section: Discussionmentioning
confidence: 98%
“…Kovac et al [11] reported a complete response (CR) rate (no nausea and no vomting at any time interval) of 56% of patients who had received a dose of palonosetron 0.075mg. Candiotti [13] reports a CR rate of 43% at 0-24 h after surgery and 49% at 24-72h after surgery. This is consistent with the 60% success rate in the Pal group that we report in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation